3,9-Di-2-furyl-2,4,8,10-tetraoxaspiro[5.5]undecane - Jun Lin (Acta Crystallographica Section E, 2008)
The title compound, C15H16O6, was prepared by reaction of 2,2-bis(hydroxymethyl)propane-1,3-diol with 2-furaldehyde in the presence of hydrochloric acid at room temperature. The asymmetric unit contains two crystallographically independent molecules. In these two molecules, the dihedral angles between the five-membered rings are 56.4 (3) and 56.3 (3)°. The six-membered rings adopt chair conformations. Intermolecular C—H...π interactions link the molecules and may be effective in the stabilization of the crystal structure.